2022
DOI: 10.3389/fchem.2022.912550
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Metal-Support Interactions Between CuxO and ZnO for CuxO/ZnO Catalysts With Enhanced CO Oxidation Activity

Abstract: Metal-support interaction has been one of the main topics of research on supported catalysts all the time. However, many other factors including the particle size, shape and chemical composition can have significant influences on the catalytic performance when considering the role of metal-support interaction. Herein, we have designed a series of CuxO/ZnO catalysts as examples to quantitatively investigate how the metal-support interaction influences the catalytic performance. The electronic metal-support inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…However, this would not explain the case when the oxide phases are found separately. Recent studies have resumed the analysis of this aspect and confirmed a synergy between CuO-ZnO [34], which is attributed to electron transfer from ZnO to CuO, generating electron-rich heterojunctions, which are more favorable for the adsorption and dissociation of oxygen and the subsequent CO oxidation. Recently, the catalytic behavior of ZnO crystals with different morphologies onto which small CuO nanoparticles were dispersed was analyzed.…”
Section: Catalytic Performance Of Cuznni Oxides Filmmentioning
confidence: 99%
“…However, this would not explain the case when the oxide phases are found separately. Recent studies have resumed the analysis of this aspect and confirmed a synergy between CuO-ZnO [34], which is attributed to electron transfer from ZnO to CuO, generating electron-rich heterojunctions, which are more favorable for the adsorption and dissociation of oxygen and the subsequent CO oxidation. Recently, the catalytic behavior of ZnO crystals with different morphologies onto which small CuO nanoparticles were dispersed was analyzed.…”
Section: Catalytic Performance Of Cuznni Oxides Filmmentioning
confidence: 99%